2015
DOI: 10.2174/1389200216666150812123725
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Drug Reactions to Anti-TB Drugs: Pharmacogenomics Perspective for Identification of Host Genetic Markers

Abstract: Adverse drug reactions (ADRs) are associated with clinical morbidity and, in severe cases, even mortality. Globally billions of dollars are spent on managing these ADRs for common and uncommon diseases. The developing world suffers from a high burden of tuberculosis, which requires 6-8 months of multi-drug treatment. In spite of most cases being treatable the problem persists mainly due to a high attrition rate associated with ADR mediated complications. Due to these reasons drug resistant strains have emerged… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 0 publications
1
9
0
Order By: Relevance
“…This variant could result in interindividual variability of CYP2D6 enzymatic activity or expression. Previous studies and our results suggest that the CYP2D6 gene may play a role in participating in the metabolism of ATDs or forming covalent adducts with ATDs, similar to the effect of some other general CYP enzymes on ATDs; however, this possibility should be verified in functional assays.…”
Section: Discussionsupporting
confidence: 50%
“…This variant could result in interindividual variability of CYP2D6 enzymatic activity or expression. Previous studies and our results suggest that the CYP2D6 gene may play a role in participating in the metabolism of ATDs or forming covalent adducts with ATDs, similar to the effect of some other general CYP enzymes on ATDs; however, this possibility should be verified in functional assays.…”
Section: Discussionsupporting
confidence: 50%
“…The first finding is somehow surprising because a less expressed OATP1B1 is associated with lower intrahepatic exposure of RIF. Because several studies demonstrate that liver injury is not linked to plasma exposure, our initial hypothesis was that alternative causes (such as hepatic or intracellular concentrations or specific metabolites) may link genetic variants to liver toxicity . On the contrary, PXR has been shown to modulate hepatotoxicity associated with RIF and INH cotherapy in a mouse model .…”
Section: Discussionmentioning
confidence: 99%
“…Because several studies demonstrate that liver injury is not linked to plasma exposure, our initial hypothesis was that alternative causes (such as hepatic or intracellular concentrations or specific metabolites) may link genetic variants to liver toxicity. 29 On the contrary, PXR has been shown to modulate hepatotoxicity associated with RIF and INH co therapy in a mouse model. 30 Although the exact mechanism has not been clarified, it may be related to the induction of CYPs (as shown by the presence of anti-INH, anti-CYP2E1, anti-CYP3A4, and anti-CYP2C9 antibodies) or through the PXR-mediated perturbation of heme biosynthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to other side effects such as hepatotoxicity, pharmacogenetic factors prone to develop anti‐TB drug‐induced hyperuricemia and gout have not been investigated in depth. A recent review article has reported the high frequency of occurrence of single nucleotide polymorphisms of URAT1 gene in PZA‐related hyperuricemia, but their clinical relevance is as yet unclear . Further studies regarding the interactions between anti‐TB medications and certain genetic polymorphisms related to uric acid transport will be needed in the future.…”
Section: Discussionmentioning
confidence: 99%
“…9 Additionally, patients' genetic factors may influence the occurrence vance is as yet unclear. 23 Further studies regarding the interactions between anti-TB medications and certain genetic polymorphisms related to uric acid transport will be needed in the future.…”
Section: Discussionmentioning
confidence: 99%